Human Vulnerabilities to Social Engineering Attacks: A Systematic Literature Review for Building a Human Firewall - Tsauri, Muhammad Shofian (Journal of Applied Informatics and Computing, 2025)
Social engineering attacks exploit human psychology to deceive individuals into compromising information security, making the human element a critical vulnerability in cybersecurity systems. This study aims to identify and analyze patterns of human susceptibility in social engineering through a systematic literature review (SLR). Guided by the PRISMA 2020 protocol, a total of 865 articles were initially retrieved from databases such as Scopus, IEEE Xplore, ResearchGate, and Google Scholar. After applying strict inclusion and exclusion criteria, 39 peer-reviewed articles published between 2020 and 2024 were selected for thematic synthesis. The results reveal recurring human vulnerability factors including low security awareness, emotional manipulation (e.g., fear, urgency), overtrust in authority, and lack of behavioral control. These vulnerabilities manifest in predictable victim profiles and behavioral patterns, which are often exploited through phishing, pretexting, and other deception-based tactics. Furthermore, the review highlights the limitations of current mitigation strategies that focus solely on technical solutions without integrating human behavior models. The findings serve as a conceptual foundation for building a “human firewall,” emphasizing awareness, vigilance, and behavioral training as integral components of social engineering defense. This study also lays the groundwork for the development of a human-centric detection model in future research, particularly in the context of mobile banking.